Developing and exploring the characteristics of optical-fibre vibration sensor (Nexo Revista Científica, 2021)
Integration of optics into microelectronics is extremely attractive in terms of further microminiaturisation and information transmission rate. Hence, the article aims at opening up and studying all the opportunities that can be taken from a simple optical sensor that is based on reflection of light from an oscillating surface.To measure vibrations, a principle of determining the amplitude of a diverging cone of light has been employed depending on the distance to an oscillating surface. The most common optical fibre with the numerical aperture of 0.12 was used in the experiments. The wavelength of laser utilised in the sensor is 1310nm. A laser with 640nm wavelength was used in the control stand measurement path. The conducted studies resulted in creating a simple vibration sensor on the basis of optical fibre with the use of laser, photo-diode, and splitter. It has been experimentally shown that the amplitude of the reflected light changes exponentially depending on the distance to the oscillating surface. The accuracy of interferometric measurements was 22nm. The coherence length of lasers used in the interferometer amounted to 2mm, what well sufficed to obtain a contrast interference pattern. Vibrations of various surfaces from 500µm to 22nm were measured. A major plus of the sensor is its maximum ease and a rather high accuracy of measurements. Measured frequency of vibrations is limited only to the transfer characteristic of an electronic part of the sensor. The article materials are of practical value for using their principles in micro-accelerometers, angular velocity sensors, and many other sensors of physical values.